PERTANGGUNGJAWABAN KETERLAMBATAN PENERBANGAN AKIBAT PENGGANTIAN JENIS PESAWAT UDARA YANG DILAKUKAN OLEH PENGANGKUT (CONTOH KASUS: TIDAK TERANGKUTNYA PENUMPANG PADA PENERBANGAN LION AIR JT-1341 TAHUN 2018) - Fakhri Nur Akmal; H. K. Martono (Jurnal Hukum Adigama, 2019)
Indonesia is an archipelagic country that can be divided into land, water and airspace. For the sake of realizing a national insight, it requires a transportation system. Transportation can be divided into land, sea and air transportation. Air transportation is a very efficient transportation for humans because it has comfort and can save time.Air transportation growth in Indonesia are rising highly time by time, law must provide the rule of operation of air transport. Passenger have right to get to destination that ruled on air ticket. Beside of the destination, passenger must get delivered by the time that written on ticket. Airline must provide aircraft that could carry all passenger that have the ticket, but in practice, some passenger cant be carried by airline because there was changes of the type of aircraft that carry less passenger than planned. Passenger must get compensation from the loss. Airline shall responsible from causing the trouble. There were some responsibility system in Indonesia law, but for the case of the above, the responsibility system that should airline take is unclear. This journal will discuss about the responsibility system that can be used for the case and how law govern to clear the problem.